Análise do impacto de sistemas integrados de gestão na maturidade organizacional em empresas de construção civil - Mainardes, Christiane Wagner (2013)
The construction companies have used the integrated management systems, especially ERP, to improve its processes, in order to increase the gains in productivity and quality, reduce costs and create competitive advantages. However, deploying such a system entails a major organizational change, which explains the fact that some companies give good results and some not. This research identifies which variables associated with the processes of deployment, management and performance of the ERP system interfere with variables associated with organizational maturity in construction companies. This objective was achieved by conducting a descriptive research and quantitative in 106 construction companies throughout Brazil that use ERP system or not. Analyzed the results using statistics with descriptive analyzes and multivariate analyzes. Pearson correlation and discriminant analysis techniques were used for multivariate analysis. The results show that ERP implementation impacts on the variables of organizational maturity in the following aspects: strategic vision, customer relationship management, human resources, IT management and financial management. Organizations using ERP have a higher growth rate and number of clients, recognition of "brand", high level of training of the management, integration between departments and processes, better information flow, greater formalization of activities and processes, more planning activities and better management of human resources.